CAMELLIA INUSITATA (THEACEAE), A NEW SPECIES FORMING A NEW SECTION (BIDOUPIA) FROM VIETNAM - Orel, G.; Wilson, P. G.; Curry, A. S.; Truong, Luu Hong (Edinburgh Journal of Botany, 2012)
A new species of Camellia L. (Theaceae) from Vietnam, C. inusitata Orel, Curry & Luu, is described, illustrated and compared with six Camellia species from sections Thea (L.) Dyer, Corallina Sealy and Paracamellia Sealy. Reproductive morphology and molecular evidence supports taxonomic placement in the genus Camellia but the vegetative morphology is so distinct that a new section, Camellia sect. Bidoupia Orel, Curry & Luu, is established.
Keywords: Camellia; IUCN Red List; Theaceae; Vietnam